2020
DOI: 10.1101/2020.06.08.140426
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiplexed imaging of human tuberculosis granulomas uncovers immunoregulatory features conserved across tissue and blood

Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that is distinctly characterized by granuloma formation within infected tissues. Granulomas are dynamic and organized immune cell aggregates that limit dissemination, but can also hinder bacterial clearance. Consequently, outcome in TB is influenced by how granuloma structure and composition shift the balance between these two functions. To date, our understanding of what factors drive granuloma function in humans is limited. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 74 publications
2
42
0
Order By: Relevance
“…Subcluster 11 was relatively abundant (2.4% of granuloma cells, Table S4C) and was characterized by expression of transcripts associated with cellular proliferation (MKI67, STMN1, and TOP2A) ( Figure 3C-D, Table S8B), consistent with published data that T cell proliferation occurs within NHP and human granulomas (Gideon et al, 2015;McCaffrey et al, 2020;Ohtani, 2013;Phuah et al, 2016;Phuah et al, 2012;Wong et al, 2018). Subcluster 12, representing 0.6% of granuloma cells, is characterized by enrichment of genes associated with nuclear speckles and splicing factors such as PNISR and SRRM2 ( Figure 3C), the latter of which has been associated with alternate splicing in Parkinson disease (Shehadeh et al, 2010) and has a critical role in organization of 3D genome (Hu et al, 2019).…”
Section: Additional T/nk Cell Subclusters That Correlate With Controlsupporting
confidence: 88%
“…Subcluster 11 was relatively abundant (2.4% of granuloma cells, Table S4C) and was characterized by expression of transcripts associated with cellular proliferation (MKI67, STMN1, and TOP2A) ( Figure 3C-D, Table S8B), consistent with published data that T cell proliferation occurs within NHP and human granulomas (Gideon et al, 2015;McCaffrey et al, 2020;Ohtani, 2013;Phuah et al, 2016;Phuah et al, 2012;Wong et al, 2018). Subcluster 12, representing 0.6% of granuloma cells, is characterized by enrichment of genes associated with nuclear speckles and splicing factors such as PNISR and SRRM2 ( Figure 3C), the latter of which has been associated with alternate splicing in Parkinson disease (Shehadeh et al, 2010) and has a critical role in organization of 3D genome (Hu et al, 2019).…”
Section: Additional T/nk Cell Subclusters That Correlate With Controlsupporting
confidence: 88%
“…The workflow outlined in Figure 1 enabled high-dimensional, subcellular imaging of dozens of proteins that recapitulated the tissue architecture observed in H&E ( Figure 2A). Multiplexed imaging data were processed with a low-level pipeline prior to singlecell segmentation ( Figure 2B, Figure S2B) (Keren et al, 2018;McCaffrey et al, 2020;Moen et al, 2019;Valen et al, 2016), which identified on average ~924 cells in each FOV (sd = 317). To determine cell location with respect to canonical histological features, we demarcated duct, stroma, and myoepithelial regions of each image based on combinatorial marker expression ( Figure 2B bottom-right).…”
Section: A Single Cell Phenotypic and Spatial Atlas Of Dcismentioning
confidence: 99%
“…Antibodies were conjugated to isotopic metal reporters as described previously (Keren et al, 2018;McCaffrey et al, 2020). Following conjugation antibodies were diluted in Candor PBS Antibody Stabilization solution (Candor Bioscience).…”
Section: Antibody Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This diversity of data allows models trained on TissueNet to handle data from many different experimental setups and biological questions. The images included in TissueNet were acquired from the published and unpublished works of labs who routinely perform tissue imaging [44][45][46][47][48][49][50][51] . Thus, while this first release of TissueNet encompasses the tissue types most commonly analyzed by the community, we expect that subsequent versions of TissueNet will be expanded to include less-studied organs.…”
Section: A Human-in-the-loop Approach Drives Scalable Construction Ofmentioning
confidence: 99%